PENGGUNAAN PRODUK E-TOLL TERHADAP KUALITAS PELAYANAN PADA GERBANG TOL CILILITAN - Yuliantini Yuliantini; Wolfhardus Octavianus Basi; Payaman Manik (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
This study aims to determine the effect of e-toll on the quality of service at Cililitan toll gate. The research method used descriptive verification with data analysis using simple linear regression. Primary data was obtained through direct survey to e-toll users at Cililitan toll gate, Jakarta, with a sample of 50 respondents. The result of the research shows that the use of e-toll has a positive and significant effect on the service quality of Cililitan toll gate, Jakarta. The limitation of this research is that the influence of e-toll usage is not only influenced by service quality but can be influenced by other factors. It is necessary to do further research related to those other factors by developing the study at other toll gate so that the standard of Automatic Gate Service (AGS) can be applied to toll services.